MUSEUM FOR SOCIETY: EXPERIENCE OF NATIONAL MUSEUM OF EDUCATION IN GABROVO - Burceva, Rita; Karagiozova, Maya; Nedkova, Dasa (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2016)
The direct didactic interpretation of the educational activity of museums has exhausted itself, therefore these cultural institutions should turn to more current methods of promotion of material and non-material heritage along with the tradition forms of activity. The purpose of the research is to establish and analyse the possibilities of museums in terms of public education, making use of the modern technologies. Methods: theoretical literature analysis, collaborative field research, case analysis.The National Museum of Education of Bulgaria in Gabrovo is famous for its artefacts, which characterise the historical development of education in Bulgaria since the 9th century. Therefore this museum is unique in Europe. As a result of the digitization of the museum’s collection it can offer extensive information opportunities and tools to the visitors and users of the museum. According to the legislative changes of 2016, the functions of the National Museum of Education are also expanded, and it becomes a special link of support in the education system of Bulgaria, developing the Centre for Study Visualisation. An innovative element of the museum’s activity is the professional development and dissemination of study visualisation for the purpose of enriching the choice of teaching aids (education films, multimedia presentations, tables and schemes, exhibitions) for use in the study process at general education establishments. The development of such planned, coordinated, state financed and corresponding to the demand study visualisations is an example of good practice of the contribution of the National Museum of Education in public education and it creates bases for adopting the positive experience in other countries.